The Static City: The Portrayal of Stasis in Conchitina Cruz’s Dark Hours - Banzon, Sharleen (Journal of English Studies and Comparative Literature; Vol 9 No 1 (2006), 2007)
Excerpt The project of this study is to examine the techniques employed in the writing and arrangement of poems in a collection that presents a characteristic societal flaw of a particular place and its representative people and culture. My particular city of interest is Manila, and the particular characteristic flaw of this city that I intend to focus on is stasis. The primary text I will be analyzing is Dark Hours , a collection of prose poems by Conchitina Cruz. The kind of stasis presented in Dark Hours is not necessarily a lack of movement; it is principally the city’s lack of progress that is portrayed. Although the name of the city in Dark Hours is not specified, certain details in the text indicate that the city being written about is Manila. I have chosen Dark Hours because its characterization of stasis may be seen not just in the individual poems but also in the way the poems are arranged in the collection. The result is that while in each poem the stasis is presented through a particular situation or incident involving a single character, when read as a collection, the poems form a complete picture of the city’s condition as it is influenced by its residents’ actions and as it influences its residents’ lives.